Overall Performance of Malaysian Futures Market: Evidence Using Crude Palm Oil and Stock Index Futures Contract - Chowdury, Taufiq Hassan Shah (2001)
This research analysed four important issues relating to the efficiency of futures market, namely pricing characteristics, informational role, arbitrage efficiency and hedging performance of two important derivative products namely crude palm oil futures (CPO) and stock index futures contracts (SIF). Daily data on CPO contracts for the calendar years 1987 through 1998 and 1996 through 1999 for stock index contracts were used. Several hypotheses concerning the pricing behaviour of futures contracts (CPO and SIF) were tested to ascertain whether the pricing behaviour is consistent with theory in the context of an emerging market. The fmding suggests that the pricing behaviour of CPO futures is consistent with theory over the whole period of analysis. And the liquidity increased with volume for the CPO futures. Delivery month does not have any significant impact on price volatility. For stock index futures, the pricing behaviour is not stable over time possibly due to the financial crisis (July 1997 to September 1998) and/or more importantly, due to the learning period effect. The liquidity of this contract did not increase with the increase in volume probably due to the lack of speculators. Excepting in a sub-period (1993-1995), the findings suggest that information is a major determinant of cash price movement of CPO contracts. For stock index futures, significant informational linkages between cash and futures prices is observed only after the financial crisis. There was no informational link between cash and futures markets before the crisis. In terms of arbitrage efficiency, the CPO futures show weak arbitrage activity. Spot volatility reduces the spread between cash and futures though it was not simultaneous while futures volatility does not have an important role in reducing the spread. For stock index futures, spot volatility as well as futures volatility simultaneously reduces the spread in the post crisis period. In the pre crisis period, these contracts showed